2003
DOI: 10.1046/j.1365-2699.2003.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

A regional impact assessment of climate and land‐use change on alpine vegetation

Abstract: Aim Assessing potential response of alpine plant species distribution to different future climatic and land-use scenarios.Location Four mountain ranges totalling 150 km 2 in the north-eastern Calcareous Alps of Austria.Methods Ordinal regression models of eighty-five alpine plant species based on environmental constraints and land use determining their abundance. Site conditions are simulated spatially using a GIS, a Digital Terrain Model, meteorological station data and existing maps. Additionally, historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
279
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(304 citation statements)
references
References 92 publications
12
279
1
12
Order By: Relevance
“…As Gottfried et al (1998) have noted, high altitude specialist species, if widespread (like Androsace alpina) will reach such refugia habitats; but rare species will probably become extinct on some mountains. Dirnböck et al (2003) support the hypothesis that alpine plant species with restricted habitat availability will experience severe fragmentation and habitat loss. They showed that this would only occur if temperatures increase by 2 K or more.…”
Section: Discussionsupporting
confidence: 76%
“…As Gottfried et al (1998) have noted, high altitude specialist species, if widespread (like Androsace alpina) will reach such refugia habitats; but rare species will probably become extinct on some mountains. Dirnböck et al (2003) support the hypothesis that alpine plant species with restricted habitat availability will experience severe fragmentation and habitat loss. They showed that this would only occur if temperatures increase by 2 K or more.…”
Section: Discussionsupporting
confidence: 76%
“…This fact has implications both for modelling treeline responses to climate change and as evidence of the potential biodiversity loss that likely will involve the treeless alpine belt vegetation in mountain environments because of fragmentation and habitat loss (Theurillat and Guisan 2001;Dirnböck et al 2003;Kullman 2010). A treeline upward advance by 200-600 m has been estimated for the next 100 years in the Swedish mountain region: a climatically driven change that could cause a 75-85% of reduction of the alpine areas, with most of the remaining area being constituted by scree slopes and boulder fields (Moen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the European Alps and, more in general, in Europe, where there are no ecosystems that are totally undisturbed by human activities, ecological studies must take into account both changing land use and changing climate [11,49,56].…”
Section: Discussionmentioning
confidence: 99%